If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -4) + 2 = 42 Reorder the terms: 2(-4 + 3x) + 2 = 42 (-4 * 2 + 3x * 2) + 2 = 42 (-8 + 6x) + 2 = 42 Reorder the terms: -8 + 2 + 6x = 42 Combine like terms: -8 + 2 = -6 -6 + 6x = 42 Solving -6 + 6x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = 42 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 42 + 6 6x = 42 + 6 Combine like terms: 42 + 6 = 48 6x = 48 Divide each side by '6'. x = 8 Simplifying x = 8
| 2x-3=-20x | | 2x-3=-20 | | 2x-3=4*2 | | =15+273.15 | | 8000/4 | | X+(X*0.05)=1068 | | 5x+8=60-125x | | (2x-1)=3(x+7) | | 9x+7y+17z=107 | | 4-(15-2x)=3(2x-9-2(9-x)) | | 4x^2-3x+12=0 | | 60x+1=3(3+4x) | | 60x+10=80x-6 | | 36=2l+2w | | -21=7+6(c+5) | | 10x+1=12x-17 | | -6(7-9x)=-21 | | 6.8x=18000+(2x) | | -3+6(1+9v)=-28 | | -270=-5(9x-9) | | x/-12+4=9 | | y/3+18=70 | | 114-9x=-6x-156 | | -31=-6(3d+5) | | -22-3x=54+x | | -9b+5b=34 | | 171+5x=-6x-156 | | 2x-4(3x-3)=92 | | -4(8a+7)=23+5a | | 9x-53=12x+28 | | 51-5x=-63+x | | 0,25(4x-3)=3-x |